2009
DOI: 10.1212/wnl.0b013e3181b2a4f5
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive contributions to verbal fluency deficits in frontotemporal lobar degeneration

Abstract: Objective: To test the hypothesis that different neurocognitive networks underlie verbal fluency deficits in frontotemporal lobar degeneration (FTLD).Methods: Letter ("FAS") and semantic ("animal") fluency tests were administered to patients with a behavioral/dysexecutive disorder (bvFTLD; n ϭ 71), semantic dementia (SemD; n ϭ 21), and progressive nonfluent aphasia (PNFA; n ϭ 26). Tests measuring working memory, naming/lexical retrieval, and semantic knowledge were also obtained. MRI voxel-based morphometry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
81
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 42 publications
8
81
2
1
Order By: Relevance
“…13 Moreover, overlapping left IFC and aSTC thinning for nonfluent speech and grammatic difficulty is consistent with our observation finding that difficulty producing syntactically complex structures contributes to nonfluent speech in PNFA. While prior work has related reduced category naming fluency to left frontal regions in PNFA, 15 the neuroimaging results of the present study did not reveal an overlap between areas of thinning related to nonfluent speech and areas of thinning related to category naming fluency. We are unaware of prior work directly relating speech-sound errors to cortical atrophy in PNFA, although a study of stroke patients has associated AOS with left insula stroke.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…13 Moreover, overlapping left IFC and aSTC thinning for nonfluent speech and grammatic difficulty is consistent with our observation finding that difficulty producing syntactically complex structures contributes to nonfluent speech in PNFA. While prior work has related reduced category naming fluency to left frontal regions in PNFA, 15 the neuroimaging results of the present study did not reveal an overlap between areas of thinning related to nonfluent speech and areas of thinning related to category naming fluency. We are unaware of prior work directly relating speech-sound errors to cortical atrophy in PNFA, although a study of stroke patients has associated AOS with left insula stroke.…”
Section: Resultscontrasting
confidence: 99%
“…15,28 Deficits in executive functioning have been hypothesized to interfere with strategic planning and mental search in language, and therefore potentially contribute to reduced speech fluency. 9 However, our regression analyses indicated that executive functioning does not contribute to reduced WPM in PNFA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Executive control is often evaluated by tests of verbal fluency [7,8]. Verbal fluency refers to the ability to generate words from a semantic category (e.g., animals, groceries, fruits) or a specified letter of the alphabet within a limited time.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the differences in clinical subtypes of FTD and PPA, a disparate pattern of impairment in verbal fluency tasks is expected. Indeed, a previous study showed that patients with semantic variant PPA were more impaired on semantic than letter fluency, whereas patients with bvFTD and nonfluent/agrammatic variant PPA were equally impaired in both types of tasks [8]. …”
Section: Introductionmentioning
confidence: 99%